Nezaznane priložnosti: GEM Slovenija 2012 - Rebernik, Miroslav; Tominc, Polona; Crnogaj, Katja; Širec, Karin; Bradač Hojnik, Barbara (University of Maribor Press, 2013)
Unperceived Opportunities : GEM Slovenia 2012. Global Entrepreneurship Monitor (GEM) has been researching entrepreneurship since 1998 and its aim is to provide a consistent framework for the research of entrepreneurship, particularly because the role and the significance of entrepreneurship vary depending on the level of economic and social development. Different levels of socio-economic development of countries mean different requirements as regards the most efficient ways of management as well as the most rational decisions of an individual to enter entrepreneurship. For that reason, it is impossible to give a unified advice about how to encourage entrepreneurship in all countries. This time, the study points out that Slovenia compared with other innovation countries still lags far behind in selected areas of entrepreneurial environment, and worrying is the low level of business opportunities’ perception. The study identified a gap between people’s respect for entrepreneurship as a profession and their belief that entrepreneurship is a good career choice. Among the worrying findings are the low level of women entrepreneurs and the lowering educational structure of entrepreneurs. Among the positive findings it is that the opportunity entrepreneurship is increasing.